The Effect of Educational Exercises According To The Motor Coding Strategy (Performance) In Learning The Skill of Handstand (Journal of the College of Basic Education, 2025)
The study aimed to prepare educational exercises according to the strategy of kinetic coding (performance) in learning the skill of handstand and identify the impact of the strategy in learning the skill where the research assumed that there are moral hypotheses of statistical significance in the results of pre- and post-tests, the researcher used the experimental approach with two equivalent groups with pre- and post-test The research community was chosen in a deliberate way The study sample was chosen randomly and was represented by students of the first grade average (boys) as it reached Their number (30) students divided into two groups for each group (15) students, as the test results showed that there are statistically significant differences between the two groups and in favor of the experimental group and the researcher recommended the need to use a strategy in learning the skill of handstand and can be used to learn ground movements in artistic gymnastics in particular and other sports in general